Silent Way Method: Improve Students’ English Vocabulary at SMK Negeri 1 Kota Ternate - Adi F. Mahmud; Alrino Ode Masimu; Faujia Umasugi (EDU Journal - English Department of UMMU Journal, 2022)
The objective of this research was to determine the implementation of the silent way method to improve students’ English vocabulary. This research used quantitative methods with a quasi-experimental design. The population is 40 students, and they are from two classes. 20 students from the Tourism major were involved as a sample of the research taken by the Cluster Random sampling technique. The multiple-choice test is used as an instrument to determine the improvement of student's English vocabulary. Data is taken in three steps: pretest, treatment, and posttest as the final step. Research data were analyzed using the t-test formula with SPSS 22. The research results showed that the pretest score from the experimental class was 61.5 and the post-test score was 68.6. While the results of the t-test showed a t-count of 1.718 with a sig. (2-tailed) of 0.007, compared with a significance level of 0.05 on the board t-table, 1.685 The comparison results show the t-count is 1.718 greater than the t-table, which is 1.685. So, it can be concluded that the Silent Way Method is effective to improve second-grade students' English vocabulary. On the other hand, the null hypothesis was rejected, while the alternative hypothesis was accepted.